Maternal thyroid function and offspring birth anthropometrics in women with polycystic ovary syndrome - Trouva, Anastasia; Alvarsson, Michael; Calissendorff, Jan; Åsvold, Bjørn Olav; Ujvari, Dorina; Hirschberg, Angelica Lindén; Vanky, Eszter (Frontiers in Endocrinology, 2024)
Objectives. Polycystic ovary syndrome (PCOS) and thyroid disorders have both been linked to adverse pregnancy and neonatal outcomes. Even small variations in thyroid function within the normal range may influence fetal growth. Our aim was to investigate whether maternal thyroid function is associated with newborn anthropometrics in PCOS and explore the potential modifying effect of metformin. Methods. Post-hoc analyses of two RCTs in which pregnant women with PCOS were randomized to metformin or placebo, from first trimester to delivery. Maternal serum levels of thyroid stimulating hormone (TSH) and free thyroxine (fT4) were measured at gestational weeks (gw) 5-12, 19, 32 and 36 in 309 singleton pregnancies. The mean z-scores of birthweight, birth length, and head circumference were estimated in the offspring. Associations of maternal thyroid parameters with offspring anthropometrics and the outcomes large for gestational age (LGA) and small for gestational age (SGA) were studied using linear and logistic regression models, with adjustment for body mass index (BMI) when relevant. Results. Maternal fT4 at baseline was negatively associated with birth length (b= -0.09, p=0.048). Furthermore, ΔfT4 during pregnancy correlated positively to z-score of both birth weight and length (b=0.10, p=0.017 and b=0.10, p=0.047 respectively), independently of treatment group. TSH at baseline and gw19 was inversely associated with LGA (OR 0.47, p=0.012 and OR 0.58, p=0.042), while ΔTSH was positively associated with LGA (OR 1.99, p=0.023). There were inverse associations between TSH at baseline and SGA (OR 0.32, p=0.005) and between ΔfT4 and SGA (OR 0.59, p=0.005) in the metformin group only. There were no associations between maternal thyroid function and head circumference of the newborns. Conclusions. In women with PCOS, a higher maternal fT4 in early pregnancy and a greater decrease in fT4 during pregnancy was associated with a lower offspring birthweight and shorter birth length. Higher TSH by mid-gestation and smaller increase in TSH during pregnancy was associated with less risk of LGA. Subclinical variations in maternal thyroid function might play a role for birth anthropometrics of PCOS offspring.